Temporary public space case study of Lanai MIP / Mohamad Suhaimi bin Khalid and Ana Kashfi Muhamad - Khalid, Mohamad Suhaimi; Muhamad, Ana Kashfi (2019)
Lanai MIP is a project that looks on the idea of a temporary public space within an urban setting. Originally an empty space with a bit of a touch on landscape, the space was then converted into a temporary attractive area in conjunction to celebrate the 9 th World Urban Forum. Using this as a case study, this research examines the contextual setting of Lanai, facilities provided and the environmental impact and further explores the possibility to convert the little place into a permanent public space where people can enjoy, relax and socialise with one another. To ensure this study can achieve its goal, several objectives were outlined, comprises of background study of public space, observation and survey using a set of questionnaire form, followed by relevant recommendations for improvement. Findings from the analysis showed a positive prospect not only to convert the area into a permanent public space, but also to further expand the boundary by reclaiming the existing road next to the area. By doing so, it is believed that the space will be more vibrant and freer from noise and air pollution., offering a mini escapade area that can also function as a pocket park for people.